Pemanfaatan Media Visual dalam Pembelajaran Bilangan Rasional dan Irasional pada Siswa SD untuk Mempermudah Pemahaman Konsep - Debby Yuliana Sinaga; Erasagita Sinaga; Uli Sabat Marbun; Putri Rezeki Simbolon; Yulita Grasia Saragih; Diska Berliana Sitorus; Putri Angelika Sinaga; Ratui Dian T P Sinaga; Norita Rusmida Siagian (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study tries to see the use of visual media in making it easier for elementary school students to understand the concept of rational and irrational numbers. The technique used in this study is a descriptive qualitative approach, using the topic of grade V or VI students and Mathematics teachers. Documentation, interviews, and observations were used to collect data. The findings show that the use of visualization media, including pictures, charts, and films, is able to increase students' understanding of rational and irrational number materials. Students are more enthusiastic, active, and confident in participating in learning. The use of visual media also strengthens student participation and creates an engaging learning atmosphere. Overall, visual media has proven to be effective in helping students understand abstract ideas in mathematics, especially rational and irrational numbers, in accordance with the Merdeka Learning curriculum-based learning approach.